ENTREPRENEURSHIP EDUCATION AND GRADUATE EMPLOYABILITY IN KOGI STATE, NIGER - Onje Samuel; Dr Joel Akowe; Dr (Mrs) Ruth Haruna A; Noah Opaluwa; Omejeh Timothy Enejoh (EPRA International Journal of Research and Development (IJRD), 2022)
The 21st century presents new problems for humanity, including globalization, the rapid rate of invention, and the rapid dissemination of technology. Along with other variables, these are altering not only how economies and businesses operate but also the nature of the labor market. Education is the most effective means available to society to challenge the future. It is widely assumed that the increasing percentage of graduate unemployment is due to a lack of required skills and competencies required by employers. To operate effectively and proficiently in the workplace, graduates must acquire the necessary capacities, knowledge, and skills. And because these skill set is lacking in most graduates; the issue of employability is brought to the table. This paper thus is to bring to light the required skill sets needed by employers of labor and how the graduates are faring as to the supply of these required skills at the sampled workstation. This paper concludes that the graduates need to do better for themselves after graduating to acquire the needed skills sought-after by these employers and also recommends a shift or readjustment of the curriculum to accommodate the required skills needed to flourish in the work place.